Retreat of Thwaites Glacier Triggered by its Neighbours - Stephen Cornford (ESS Open Archive)
The Amundsen Sea Embayment in West Antarctica is experiencing the most rapid mass loss and grounding line retreat in Antarctica. Its glaciers are vulnerable to retreat through marine ice sheet instability. There is uncertainty over the timing and magnitude of retreat and in particular the response of Thwaites Glacier to thinning of its ice shelf and to ocean forced retreat of its neighbouring glaciers. We find that the response of Thwaites to melting of its ice shelf is limited. However, retreat of its neighbours can drive substantial retreat in Thwaites. We examine the impact of ice shelf buttressing on the stability of the grounding line. Further experiments show that extreme ice shelf forcings are required to trigger retreat in Thwaites in isolation. We also demonstrate that long-term stability is sensitive to the treatment of basal stress near the grounding line.